Pengenalan dan Pelatihan Pencatatan Laporan Keuangan Dengan Aplikasi Teman Bisnis Pada UMKM di Desa Tulas, Klaten - Aprianingsih, Rista; Diana Airawaty (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
Recording financial reports is a common practice carried out by many business actors. However, MSMEs often consider it as less important. Therefore, a community service activity was held in the form of introduction and training in recording financial reports for MSMEs using the TemanBisnis application. This is caused by low knowledge, awareness and understanding of MSME actors regarding recording financial reports. This community service activity was carried out in Tulas Village, Karangdowo, Klaten. The service activities focused on 2 MSME subjects in Tulas Village who still use manual methods in recording their business financial reports. The methods applied in this service are surveys, training in recording financial reports using the TemanBisnis application, monitoring and evaluation. It is hoped that the results of this activity will make MSME players understand more about the importance of recording financial reports in business and understand how to record financial reports effectively and easily using smartphone-based applications such as the TemanBisnis application.